Concentration of heavy metals in grain of plants cultivated in soil with different contamination levels - Silva, Maria Ligia de Souza; Vitti, Godofredo Cesar; Trevizam, Anderson Ricardo (Pesquisa Agropecuaria Brasileira, 2007)
The aim of this work was to evaluate the absorption and capacity of translocation of heavy metals from the soil to rice and soybean grains. Experiment was carried out in a greenhouse using a dystrophic Typic Hapludox soil from the district of Paulínia, SP. Soil samples were collected in seven different points and were organized according to the distance from a factory, source of pollution. The experimental design used was the completely randomized, with four replications. The roots, aerial leaves and grains were submitted to humid digestion. The concentrations of heavy metals were determined by ICP-OES. Cadmium and copper concentrations in the grains were at normal levels for both cultures, however manganese and zinc concentrations were in excess, according to the levels of soil contamination, possibly being able to reach top trophic levels. The roots limited the translocation of cadmium, copper, iron and lead to the aerial parts of both cultures. Although the translocation of lead was also limited by the roots, it was present in high concentrations in soy grains and, well as manganese and zinc, it can reach the food chain.